Servicios turísticos de agencias de viajes, centro histórico de Trujillo, que determinan la situación actual del turismo de tercera edad. - Neyra López, Rocío Del Pilar (2019)
This thesis called: TRAVEL AGENCIES TOURIST SERVICES, TRUJILLO HISTORICAL CENTER, THAT DETERMINE THE CURRENT SITUATION OF THE THIRD AGE TOURISM, is to identify and analyze the tourist services offered by the agencies. Bearing in mind that tourism for the elderly has to have specific characteristics, a contrast was made with reality, in order to know what the current status of tourist services offered by travel agencies is. We found that the specialized transportation service offered by the travel agencies of the Historic Center of Trujillo lacks adequate equipment to provide a service to tourists of the third age, the minivans do not have reclining seats, the buses do not have air conditioning and in both cases the kit does not have the necessary medication for seniors. With regard to the tourist package all luido can be mentioned that the travel agencies of the Historic Center of Trujillo have regular tourist packages that are offered to all types of tourists where not all has the all-inclusive. In relation to the specialized guidance service provided by the travel agencies of the Historic Center of Trujillo, it can be said that the guides are trained to provide a quality service, they have mastery of the information provided as well as being supported by panels and a photographic album. to be able to give a better information to the tourist of the third age, they have a good handling of the tone of the voice and the interaction that they have with the tourist, although on the other hand they lack training of first aid if in case it was needed. Finally, the service of specialized personnel in health of the third, the travel agencies of the Historical Center of Trujillo do not offer this type of service, which leads to the tourists of the third age have to hire specialized geriatric personnel before any eventuality during your trip, the travel agencies of the Historical Center of Trujillo allow nurses to accompany the tourists of the third age and give them the assistance they need. It should be noted that the research has made it possible to identify the services that travel agencies have and what options they offer to senior citizens at the time they are going to hire a tour package. Descriptive research was used and through this an analysis was made of the characteristics of tourist services offered by travel agencies for the elderly tourist. The main source of information was the owners and / or administrators of the travel agencies, who provided information about the services they provide to the elderly. The results found were made known through pictures, images, comments and analysis. It is concluded that the services provided by the travel agencies of the Historic Center lack specialized services to provide tourism to the elderly.